Correlation between High Sensitivity-Crp Level and Executive Function Disorders in Elderly Patients - Muhammad Hamdan1 , Joseph Ekowahono Rahardjo1 , Yudha Haryono1 , Devi Ariani Sudibyo1 , Dyah Anetta (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: C-Reactive Protein is a marker of inflammation and vascular disease. The high serum of high sensitivity C-Reactive Protein (hs-CRP) concentration was associated with interruption the integrity of the frontal-subcortical circuit. Objective: To determine the correlation between high serum concentration of hs-CRP and executive function disorder in elderly patients. Method: Thirty six elderly patients was examined by using a case control study. The subjects were enrolled from the out-patient at Neurology Departement Dr. Soetomo General Hospital, Surabaya, Indonesia. The time period was 4 months (April to July 2015). Executive function was measured with the Trail Making Test B (TMT B) and divided into two groups, case and control. Complete blood count and serum hs-CRP concentration were measured from nonfasting blood samples. Chi-square test was used for data analysis. Results: Eighteen subjects were enrolled in the case group (3 men, 15 women) and the other 18 subjects were enrolled in the control group (4 men, 14 women). Executive function disorder was found in 17 (94,4%) subjects of case group and 11 (61,1%) subjects of control group. High levels of hs-CRP was not associated with executive function, with p = 0,149 and adjusted OR 5,629 (CI 95% 0,538-58,860). Conclusion: These data suggested that high levels of hs-CRP was not associated with executive function in elderly patients.